Training to Improve the Ability of Destana Volunteers to Bandage Splints in Disaster Response Situations - Yeni Nur Rahmayanti; Eka Novitayanti; Fadma Aji Pramudita; Pipi Anonyma (Asosiasi Profesi Multimedia Indonesia, 2025)
A disaster is an event that causes damage, ecological disruption, loss of human life, and deterioration of health services or services on a certain scale that requires a response from the community in the disaster-affected area. Matesih District is dominated by steep slopes and experiences high rainfall. These conditions cause extensive erosion, weathering and landslides. The purpose of this service is to improve the knowledge and skills of volunteers about splint dressing. Disasters that have occurred in the world include landslides that have caused several people to suffer minor injuries. Injuries to residents generally occur in the musculoskeletal system. To prevent injuries to the musculoskeletal system, splint dressing assistance is needed through health education/training. providing understanding and knowledge to volunteers about the importance of increasing volunteer knowledge and skills about splint dressing. The method used is by presenting material and a simulation. Based on this identification, STIKes Mitra Husada Karanganyar aims to provide an understanding to Destana volunteers about splint dressing. In this service activity, the population was 27 volunteers in Girilayu village. This activity was carried out with the initial method of providing material and then continued with simulations related to splint dressing. The results of the community service activities went smoothly, understanding and skills about splinting increased by 85,2 %. So it can be concluded that the increase in splinting skills is inseparable from the provision of splint dressing training.